Evaluation and comparison of geometrical accuracy of parts produced by sintering-based additive manufacturing processes. Issue 9 (February 2017) - Fahad, Muhammad; Hopkinson, Neil
Abstract Processes that manufacture parts in an additive manner (i.e. additive manufacturing) have gained much attention in the past two decades due to their complex shape production abilities and tool-less processing. A large number of additive manufacturing processes have been commercialised since the inception of these technologies in the mid-1980s. Selective laser sintering is one of the commercially established and widely used additive manufacturing processes that has the ability to process a wide variety of materials (polymers, metals and ceramics). However, due to the use of laser, the process is slow and expensive. A novel process by replacing the laser with an infrared heater has been developed by the name of high-speed sintering. In this paper, an attempt has been made to evaluate and compare the geometric accuracy of parts built by both of these sintering processes using benchmark geometry. Results show that the accuracy of both of these processes is comparable. Also, the high-speed sintering process can build parts quickly, but the involvement of complex heat and mass transfer phenomena needs to be further studied to increase the accuracy of the parts produced.